Study Literature: Acacia Plants Lower Blood Sugar - Tedi, Tedi (International Journal Scientific and Professional, 2023)
Background: Diabetic is a chronic disease that occurs because the pancreas cannot produce enough insulin or the body cannot use insulin actively which results in high blood sugar levels. One way to prevent diabetes is to provide non-pharmacological therapies such as the use of herbal plants. One of the herbal plants that can be used in the prevention of diabetes is the acacia plant (Acacia Nicoleta). Method: The method used a literature study with a search from various sources, such as academic journals, and online articles. A literature search was carried out using keywords related to Acacia Nicoleta and diabetes. Result: in a literature review acacia can lower blood sugar levels because acacia plants contain carbohydrates, proteins, and minerals as well as secondary metabolites in the form of alkaloids, tannins, and saponins. Conclusion: acacia plant is proven to reduce blood sugar so it is expected to use the acacia plant as a non-pharmacological therapy in diabetics.